Concept of Atma Nirbhar Bharat Abhiyaan and its relevance - Kumar, Sanjay (U.S.I. Journal)
The covid pandemic, despite all its socio-economic disruption, has opened new avenues for India to chart its way towards a self-reliant and sustainable country. India has opted to turn adversity into opportunity, and is, hence, moving towards realisations of Atma Nirbhar Bharat. It has clearly spelt out that Atma Nirbhar Bharat will not be a policy of protectionism and isolationism, but a policy of India working with the world to produce for the world. PM Modi in his clarion call had clearly marked the five pillars on which the policy will stand and India has since then taken many strides towards realisation of the goal.- Reproduced
Keywords: Atma Nirbhar Bharat Abhiyaan